Trustworthiness appraisals of faces wearing a surgical mask during the Covid-19 pandemic in Germany: An experimental study - Biermann, Miriam; Schulze, Anna; Unterseher, Franziska; Atanasova, Konstantina; Watermann, Paulina; Krause-Utz, Annegret; Stahlberg, Dagmar; Bohus, Martin; Lis, Stefanie (PLOS ONE, 2021)
Background During the Covid-19 pandemic, the negative effects of wearing a mouth-nose cover (MNC) on interpersonal functioning have been discussed in public media but empirical studies on how wearing MNCs affect social judgements are sparse. In the present study, we investigated the effects of MNCs on trustworthiness appraisals, the influence of changes due to MNCs in evaluating joy, and the relationship between a social-cognitive appraisal bias and a participant’s characteristics. Methods All participants (N = 165) judged the intensity of happiness and trustworthiness in calm facial stimuli presented with and without a surgical mask covering part of the face. We analysed the relationship of changes in judgements evoked by MNCs to participants’ evaluations of MNCs as protective tools and explored their associations with the burden experienced by wearing MNCs, compliance to behaviour recommendations, their risk associated with the pandemic, and their levels of psychological distress. Results Overall, calm facial stimuli covered with MNCs were evaluated as less trustworthy and, to an even stronger extent, less happy than uncovered facial stimuli. However, participants varied in whether they showed a negative or positive evaluation of faces with MNCs; the negative bias was stronger in those participants who attributed lower protective potential to MNCs, experienced a higher burden while wearing MNCs, wore MNCs less often, and experienced a higher level of psychological distress. Conclusions A negative bias in trustworthiness appraisals of faces with a positive emotional expression covered by MNCs is linked to a participant’s evaluation of MNCs as inefficient and burdening and their experience of high psychological distress.